Ten-year experience with endobronchial ultrasound-guided transbronchial needle aspiration: single center results in mediastinal diagnostic and staging - Rosso, Lorenzo; Ferrero, Stefano; Mendogni, Paolo; Bonaparte, Eleonora; Carrinola, Rosaria; Palleschi, Alessandro; Righi, Ilaria; Montoli, Matteo; Damarco, Francesco; Tosi, Davide (Journal of Thoracic Disease, 2017)
Background: Endobronchial ultrasonography with transbronchial needle aspiration (EBUS-TBNA) is recognized as an accurate and minimal invasive procedure for diagnosis and staging of lung cancer and lymph nodal malignancies. EBUS is recommended as the first choice procedure for mediastinal staging in lung cancer in international guidelines. Methods: A retrospective evaluation was performed on single center experience with EBUS-TBNA in our thoracic surgery department in a 10-year time frame. Main indication for the procedure was suspected non-lymphomatous malignancy in intrathoracic lymph-nodes on computed tomography (CT) or positron emission tomography (PET) scan. All procedures were performed under conscious sedation in a day-hospital setting. All the aspirated specimens were obtained with a 22-gauge needle and were fixed in 10% formalin and paraffin embedded. Sections of 3 micron in thickness were cut and hematoxylin-eosin stained. Results: From October 2005 to August 2016, 496 patients were submitted to EBUS-TBNA. Number of nodal stations punctured was 592 with a mean of 2.25 punctures per patient. Diagnosis of malignancy was obtained in 291 patients (58.6%). In 25 cases a nodal metastasis from an extrathoracic primary tumor was diagnosed. Sensitivity, specificity and diagnostic accuracy were 95%, 100% and 96% respectively. Negative predictive value was 90% and positive predictive value (PPV) was 100%. When molecular tests were requested, mutational analysis was successfully performed on cell block derived material in 55 out of 56 cases (98.2%), and fluorescence in situ hybridization (FISH) analysis in 26 out of 27 cases (96.2%). Conclusions: EBUS-TBNA in our setting was an accurate and safe tool to diagnose non-lymphomatous nodal malignancies. Interestingly, in our series EBUS-TBNA has demonstrated to yield sufficient tissue for molecular analysis.